Rethinking Bargaining Power and Efficiency: A Qualitative Synthesis on Contingent Payment Mechanisms in High-Stakes Transactions - Eddy Iskandar; Harry Gozali (International Journal of Business, Marketing, Economics & Leadership (IJBMEL), 2025)
This qualitative literature review explores the strategic role of contingent payment mechanisms (CPMs) in high-stakes transactions, such as mergers, acquisitions, and technology licensing. Synthesizing insights from 58 scholarly sources across finance, strategy, and negotiation research, the study reveals that CPMs—such as earnouts, milestone payments, and royalties—serve not only as risk-sharing instruments but also as vehicles for managing bargaining power and relational uncertainty. While CPMs can promote efficiency and deal closure under information asymmetry, they also risk introducing post-deal frictions if poorly aligned with contractual enforcement or behavioral expectations. This review highlights the need to reconceptualize CPMs as dynamic tools shaped by contextual power imbalances, strategic foresight, and institutional frameworks. The findings contribute to a more nuanced understanding of how efficiency and bargaining power interact within complex, long-horizon transactional environments